A graduate recital in wind band conducting featuring analysis of: Gustav Holst's First suite in E-flat, Ney Rosauro's Japanese overture, and Daniel Bukvich's Inferno - Danielsen, Dane Holger (Kansas State University, 2010)
This document was submitted to the Graduate School of Kansas State University as a partial requirement for the Master’s of Music Education degree. It contains the historical, theoretical, performance, and rehearsal consideration, for each of the three pieces that were performed on the Graduate Student Conducting Recital on Wednesday, March 12, 2010. Selections performed on the recital included in the document’s analysis portion include First Suite in E Flat by Gustav Holst, Japanese Overture by Ney Rosauro, and Inferno by Daniel Bukvich. The analysis format for this report is based on the Blocker/Miles Unit Study technique found in the Teaching Music through Performance in Band series, as well as the Tracz concept of macro-micro score analysis. The performances of the Kansas State University Wind Ensemble served as the basis for the technical, musical, and stylistic evaluations and analysis.
Keywords: Holst; Music anaylsis; Rosauro; Bukvich; Wind band; Conducting; Education, Music (0522); Music (0413)